Pelatihan Urban Farming Untuk Meningkatkan Pemahaman Dalam Mendukung Ketahanan Pangan Masyarakat Di Bandar Lampung - Carolina, Thabita; Sundari, Susanti; Agustini; Suharyono, Heru (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2023)
This community service in the form of urban farming training aims to increase the people of Bandar Lampung's understanding of urban farming so that they are motivated to become new entrepreneurs. At least they can build family food security. The method used is Community Empowerment to increase community capacity through training. The results of this training were that 100% of participants considered this training interesting and useful, there was an increase in the understanding of participants as much as 60% who were the younger generation, most of whom were high school students along with teachers, students and the younger generation of Lazdai. They gain interesting experience and knowledge and hope there will be an advanced program that involves more young people so that a generation concerned with food security will emerge.